Antinuclear antibodies in children with Wilson's disease - O. V. Kurbatova; A. A. Zhuzhula; S. V. Lapin; M. A. Snovskaya; D. I. Kozlova; S. V. Petrichuk; D. G. Kuptsova; D. A. Kuznetsova; G. B. Movsisyan; A. D. Komarova; T. V. Radygina; A. B. Guslev; et al. (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
.